1997
DOI: 10.1159/000185498
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Differences of Serum Leptin in Obese and Normal-Weight Adolescents: Studies in Type-I Diabetes and Turner Syndrome

Abstract: The influence of exogenous insulin and estrogen substitution on serum leptin-like immunoreactivity was studied longitudinally in patients with type-I diabetes and Turner syndrome using a specific radioimmunoassay. Prepubertal, pubertal and postpubertal samples of 17 patients (9 girls, 8 boys) with type-I diabetes mellitus developing obesity were compared to those of 17 normal-weight controls matched for gender, age and diabetes duration. Six obese and six normal-weight girls with Turner syndrome were studied w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
1
6
0
1
Order By: Relevance
“…Although there was a large overlap in the range of serum leptin concentrations between boys and girls, the mean values for the whole group of males was significantly lower than for the females, in diabetics and in controls. In agreement with recent observations, we suggest that the gender differences in serum leptin concentrations, previously described in adult (15,23,24) and pediatric (12) healthy subjects, is already evident in young patients with IDDM.…”
Section: Discussionsupporting
confidence: 93%
“…Although there was a large overlap in the range of serum leptin concentrations between boys and girls, the mean values for the whole group of males was significantly lower than for the females, in diabetics and in controls. In agreement with recent observations, we suggest that the gender differences in serum leptin concentrations, previously described in adult (15,23,24) and pediatric (12) healthy subjects, is already evident in young patients with IDDM.…”
Section: Discussionsupporting
confidence: 93%
“…A distinct gender dierence in insulin sensitivity with a decreased insulin-mediated glucose utilization has been previously demonstrated in euglycaemic clamp studies, in particular in female adolescents [3]. Moreover, gender speci®c dierences of other hormones involved in weight regulation and energy expenditure such as leptin have been described in adolescents with diabetes [5]. On the other hand, psychological variables may also be of importance.…”
Section: Discussionmentioning
confidence: 76%
“…In vitro experiments using human adipocytes showed that testosterone is able to reduce leptin secretion (40), while oestradiol induces a notable increase in leptin in women, but does not alter leptin secretion in males (41). On the other hand, oestrogen substitution or suppression does not appear to increase leptin levels in normal-weight humans (19,42). Nevertheless, oestradiol does appear to be involved in the regulation of leptin levels.…”
Section: Discussionmentioning
confidence: 99%